(untitled) (AmS-Varia, 2016)
Preconceptions about the construction and function of burial mounds can heavily influence the degree of complexity one is apt to see in the field. Rather than seeing a burial mound as the result of a single moment in time, a single burial in prehistory, the mound should be considered as an entire grave field in use over a long period. The excavation of a burial mound at Hålandsmarka, in Time municipality, southwestern Norway, revealed that the monumental structure actually consisted of many different structures and was developed over the course of 2,000 years. By setting aside the standard model of a single burial centrally placed in a homogenous mound, and focusing on the processes of construction and activities that may have left recoverable traces in and around the mound, the excavation allowed for the development of new insights into the longterm use of the site before, during, and after the burials. It is argued that the situation at Hålandsmarka is not unique, and that the ability to accurately document such complexities in grave mounds is heavily dependent upon excavation strategy. It is further argued that the responsibility to document these processes must be taken into consideration in the planning of future excavations.